2019
DOI: 10.1021/acs.jafc.9b02095
|View full text |Cite
|
Sign up to set email alerts
|

6-(2-Formyl-5-methyl-1H-pyrrol-1-yl)hexanoic Acid as a Novel Retronasal Burnt Aroma Compound in Soy Sauce Aroma-Type Chinese Baijiu

Abstract: Two-step high-performance liquid chromatography (HPLC) separation in combination with taste dilution analysis was used to screen the retronasal burnt aroma compounds in soy sauce aroma-type Chinese Baijiu (Chinese traditional liquor). A major retronasal burnt aroma region was purified by Sephadex LH-20 column chromatography and HPLC separation from the soy sauce aroma-type Baijiu sample. A novel retronasal burnt aroma compound was identified as 6-(2-formyl-5-methyl-1H-pyrrol-1-yl)­hexanoic acid (1) by means of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Aroma compounds have similar structures or aroma properties and may create a superimposing effect when combined [20][21][22]. Pyrazine is a class of nitrogen-containing heterocyclic compounds, most of which have roasted aroma characteristics [35,36].…”
Section: Relationships Between Pyrazine Concentrations and Roasted Aromamentioning
confidence: 99%
See 2 more Smart Citations
“…Aroma compounds have similar structures or aroma properties and may create a superimposing effect when combined [20][21][22]. Pyrazine is a class of nitrogen-containing heterocyclic compounds, most of which have roasted aroma characteristics [35,36].…”
Section: Relationships Between Pyrazine Concentrations and Roasted Aromamentioning
confidence: 99%
“…Studies have shown that some sub-threshold aroma compounds may contribute to the overall aroma by an additive effect with supra-threshold aroma compounds [11,21]. To analyze whether sub-threshold pyrazines can affect the supra-threshold pyrazines, which in turn have an impact on the roasted aroma in SSAB, four sub-threshold pyrazines and four supra-threshold pyrazines were selected for additional tests.…”
Section: Organoleptic Impact Of Pyrazines On Ssab Aroma Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, multidimensional approaches can be used for further fractionation purposes. Two-dimensional HPLC (HPLC × HPLC), which was used successfully as a multidimensional fraction technique in identifying two new flavor components in Chinese baijiu (Zhao et al, 2018(Zhao et al, , 2019, is applicable for fractionation of wine volatile extracts. Operated in offline mode, fractionation using two-dimensional pHPLC is a two-step procedure for separated HPLC fractionations (Zhao et al, 2018(Zhao et al, , 2019.…”
Section: 2mentioning
confidence: 99%
“…These compounds are regarded as part of the backbone of Baijiu. Based on the previous flavor research, their FDs or OAVs were much higher than one, so they are generally regarded as essential compounds contributing substantially to the Baijiu flavor (Table S1; Fan et al, 2019;Niu et al, 2017;Niu et al, 2020;Song et al, 2019;Wang et al, 2019;Zhao et al, 2019). Recently, Song et al (2020) discovered that 1-butanol was not only an aroma contributor but also a marker compound for the discrimination of strong aroma-type Baijiu samples from different geographical origins.…”
Section: Introductionmentioning
confidence: 99%